Diplomacia corporativa e Relações Internacionais - Jesus, Diego Santos Vieira de (Meridiano 47 - Journal of Global Studies, 2017)
The aim of this article is to examine the concept of corporate diplomacy and explore the conceptual framework for studying this phenomenon in the field of International Relations. I also intend to explore the theoretical foundations for the study of corporate diplomacy and develop key strategies that can be adopted by corporate diplomats in order to deal with external pressures.